Evaluation Of The Policy On The Implementation Of The Mobile Driver’s License Office In Improving The Quality Of Public Services At The Depok City Police Department - Nenobais, Harry; Sugianto, Sugianto (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
The purpose of this study is to analyze and evaluate the implementation of the Mobile SIM policy in improving the quality of public services at the Depok City Police. The method used in this study is qualitative. Data collection techniques through observation, in-depth interviews, documentation and literature studies. Informants in this study consisted of the police chief, the head of the traffic unit, police, officers in the field, and community members who use the service. While the technical data analysis through data condensation, data presentation and conclusion drawing/verification. The results of this study conclude that the implementation of the Mobile SIM policy in improving the quality of public services at the Depok City Police has been running optimally, although there are still some shortcomings that need to be improved, namely such as the lack of the number of officers who provide services when the number of community members who come is greater on certain days, the need for adequate facilities, such as large and long tents to protect people who queue for services when it rains, and also the need to add to the service schedule provided so far by the Depok City Police, not only once a week but two or three times a week in each area served so far. The recommendations in this study include increasing the number of officers providing services on certain days when there are large numbers of residents, improving adequate facilities, such as larger and longer tents to protect people waiting in line for services when it rains, and expanding the service schedule currently provided by the Depok City Police, not just once a week but two or three times a week in each area served.